History education for SPM by using Augmented Reality / Siti Feirusz Ahmad Fesol and Nuraisyah Farina Atiqah Mohd Farid - Ahmad Fesol, Siti Feirusz (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
History is one of the subjects that all upper secondary students must take to sit for the Malaysian Sijil Pelajaran (SPM). However, recent research of 45 students expressed their perceptions of history subject in school found that 64% of kids disliked history subject, 45% did not exhibit interest in history, and 22% thought it was difficult to understand. Due to this, the aim of this project is to propose a new way of learning by integrating an augmented reality element in learning history subject to create more fun and engaging learning environment. The Rapid Application Development (RAD) technique is used in this application since it involves the presentation of a high number of prototypes to the user and allows for a more dependable and faster development process. The proposed solution was put to the test using a usability testing technique to evaluate the system's usability while learning History Education for Form 5 through game-based learning utilizing Augmented Reality. The findings revealed that the proposed system obtained an average score of 75.81%, indicating that the system has good, strong system usability in terms of effectiveness, efficiency, and respondent satisfaction when using the suggested application. In the future, the application may include diversify of the content and provide a knowledge of universal languages for individuals who are unfamiliar with Malay. New content must also be introduced to make game-based learning more effective at imparting knowledge.